A Development of Teaching resources: Based on West Java Ethnomathematics for Grade 7 Middle School students - Syifa Fauziah; Sirojudin Wahid (International Journal of Education and Humanities, 2021)
This study aims to develop teaching resources based on West Java ethnomathematics, while the teaching resources developed are learning modules. The method used in this study is R&D method using the ADDIE development steps (Analysis, Design, Development, Implementation and Evaluation). The finished product is validated by 2 experts. each expert is given an assessment sheet regarding the learning module. The first expert assesses the suitability of the material used in the module, while the second expert assesses the feasibility of the module from the appearance aspect. The results of the validation by the first expert stated that the module was included in the "Very good" criteria with a percentage of 91%. Similar results by the second expert stated that the module was included in the "Very good" criteria with a percentage of 88.86%. After the module is declared valid, the learning module is used by the teacher in learning activities. Tests are given to students at the beginning and the end of learning activities to assess their learning achievement. ased on the results of the Independent Sample T-test with a confidence level of 95% and = 5%, the t-value is 3.172 and the t-table is 2.00324. These results indicate that the value of t> t-table, it means that the increase in learning achievement of the experimental class is higher than the control class. Finally, it can be concluded that the use of the teaching resources is effective in improving student achievement.